Knowing Your Own Strength: Accurate Self-Assessment as a Requirement for Personal Autonomy - Anderson, J.H.; Lux, W. (Johns Hopkins University Press, 2004)
Autonomy is one of the most contested concepts in philosophy and psychology. Much of the disagreement centers on the form of reflexivity that must have to count as genuinely self-governing. In this essay, we argue that an adequate account of autonomy must include a distinct requirement of accurate self-assessment, which has been largely ignored in the philosophical focus on agents’ ability to evaluate the desirability of acting on certain impulses or values. In our view, being autonomous (i.e., self-guiding) involves understanding the extent to which one has the capacities required for one’s intended actions. On both clinical grounds (drawn from cases of frontal brain injury) and conceptual grounds, we argue that one’s autonomy is diminished to the extent to which one’s ability to assess one’s capacities is impaired.
Keywords: Wijsbegeerte; insight into illness; executive function; deficit awareness; frontal head injury; reflexivity; authenticity; compensatory strategies; anosognosia